How Motivation Shapes Speaking Ability: Insights from Eighth-Grade Students - Yunita Pratiwi, Ni Putu; Agus Pramerta, I Gde Putu; Sri Widhiasih, Luh Ketut (Journal on Studies in English Language Teaching (JOSELT), 2024)
This study explored the connection between motivation and speaking ability among eighth-grade students at SMPN 2 Kuta Utara during the 2022/2023 academic year. Out of a population of 413 students, a sample of 42 students was selected through random sampling to represent the group. To collect data, two key research instruments were employed: a motivation questionnaire to gauge the students' level of enthusiasm and determination and a speaking test focused on delivering a descriptive monologue to assess their oral communication skills. The data were analyzed using Pearson Product Moment Correlation in SPSS Statistics 25, which revealed a correlation coefficient of 0.673. This finding indicates a statistically significant and strong relationship between students’ motivation and their speaking ability, with the correlation classified as high (0.60–0.799). In essence, the more motivated the students were, the better their speaking ability tended to be. These results emphasize the critical role of motivation in language learning and suggest that fostering motivation could be a key strategy for improving speaking proficiency in English classes. Such insights could inform teaching strategies and highlight the importance of addressing both cognitive and affective factors in speaking classroom activities.